THE USE OF INTERACTIVE EXERCISES AND TASKS IN RUSSIAN LANGUAGE LESSONS IN SECONDARY SCHOOLS (Web of Technology: Multidimensional Research Journal, 2025)
This article discusses the use of interactive teaching methods in Russian language lessons in secondary schools. The essence of interactive learning is determined, the role of tasks and exercises using this method is determined.